Dismantling the rhetoric of alternative medicine: Smokescreens, errors, conspiracies, and follies - Edzard Ernst; Angelo Fasce (Mètode Science Studies Journal: Annual Review)
Alternative medicine has a high social prevalence, being promoted by well organized groups that have developed an intricate rhetoric in order to self-justify in the absence of evidence. This article will analyse some of these arguments, some of their fallacies – ad populum, ad ignorantiam –, other styles of reasoning – conspiracy theories – and other misconceptions of scientific concepts – placebo effect, scientific authority. The objective will be to highlight the poverty of the rhetoric of proponents of alternative medicine, with special emphasis on the dangers for the consumer.